CircMMD_007 promotes oncogenic effects in the progression of lung adenocarcinoma through microRNA-197-3p/protein tyrosine phosphatase non-receptor type 9 axis. Issue 3 (1st March 2022) - Zhu, Lihuan; Guo, Tianxing; Chen, Wenshu; Lin, Zhaoxian; Ye, Mingfan; Pan, Xiaojie
ABSTRACT: Circular RNAs play important roles in cancer biology. In this research, we explored the underlying function and mechanism of cirMMD_007 in lung adenocarcinoma (LC). Clinical lung adenocarcinoma samples were obtained from surgery. Bioinformatic databases were used to predict miRNAs that can potentially target circRNAs and miRNA target genes. hsa_circMMD_007, miR-197-3p, and PTPN9 mRNA expressions were investigated by qRT-PCR. Protein expressions were examined using Western blot. The proliferation abilities were assessed by Cell Counting Kit-8 assays. Wound healing cell migration assay was applied to evaluate cell migration ability. Luciferase reporter assay and rescue experiments were then performed to elucidate the underlying mechanism. We found that the expression of circMMD_007 was abnormally increased in LC. The expression of circMMD_007 was higher in advanced stages. Knockout of circMMD_007 hindered the tumorigenesis of LC in vivo and in vitro. circMMD_007 could negatively regulate the expression of miR-197-3p. PTPN9 behaved to be a molecular target of miR-197-3p. In summary, this research demonstrated that circular RNA circMMD_007 could promote the oncogenic effects in the progression of LC through miR-197-3p/PTPN9 axis. Graphical Abstract: uf0001